Synthesis of the First Representatives of Thieno[3,2-c][1,7]naphthyridine Derivatives Based on 3-Amino-6-methyl-4-(2-thienyl) pyridin-2(1H)-one - Kulakov, Ivan V.; Matsukevich, Mariya V.; Levin, Maxim L.; Palamarchuk, Irina V.; Seilkhanov, Tulegen M.; Fisyuk, Alexander S. (Synlett, 2018)
A one-pot method for obtaining novel thieno[3,2-c][1,7]naphthyridine derivatives based on the reaction of 3-amino-4-(thien-2-yl)pyridin-2(1H)-one with aromatic aldehydes in 80% phosphoric acid at 130 °C has been developed. The formation of the thieno[3,2-c][1,7]naphthyridine ring was due to the intermediate generation of the corresponding azomethine, which underwent intramolecular cyclization with electrophilic attack of the β-carbon atom of the thiophene core under Pictet–Spengler conditions. The isolated 5,7-dihydrothieno[3,2-c][1,7]naphthyridin-4(3H)-ones underwent oxidative aromatization in air to give thieno[3,2-c][1,7]naphthyridin-6(7H)-ones. A two-step synthesis of thieno[3,2-c][1,7]naphthyridines involving the isolation of the intermediate imine did not lead to a significant increase in the product yield.
Keywords: naphthyridines; aminothienylpyridinones; thienonaphthyridinones; cyclization; Pictet–Spengler reaction; oxidative aromatization